A viscoelastic cohesive zone model for starch-gluten interface to simulate dough deformation. (January 2023) - Mohammed, Mohd Afandi P.; Mokhtar, Mohd Noriznan; Wakisaka, Minato
Abstract: A viscoelastic cohesive zone model was proposed to simulate rate-dependent starch-gluten interface debonding. The debonding was believed to influence stress-strain curves of tensile and shear tests at different strain rates. The model was written as a user-defined finite element subroutine codes, which was then included into an interface element geometry between starch filler and gluten matrix. The finite element modelling results showed agreement with experimental data under uniaxial tension and simple shear at different strain rates (5/min and 0.5/min). This was due to the viscoelastic effect of the interface model, which caused difference between traction initiation at different rates for the cohesive zone model (i.e. ∼1.1kPa and ∼0.5kPa at 5/min and 0.5/min, respectively). In addition, it was shown that critical shear stress is a very important debonding parameter, where slight changes of the shear traction values caused the model stress-strain curve to deviate from the experimental results. Simulations of starch-gluten dough deformation were then conducted at different strain rates to imitate dough processes like baking, extrusion and proving (0.003/s, 1/s and 10/s, respectively). The interface model was shown to influence stress-strain curve at lower strain rate processes like baking and extrusion. Graphical Abstract: ga1 Highlights: Rate dependent starch-gluten interface damage was modelled using numerical method. Shear traction values from the interface model influenced the starch-gluten debonding. The interface model was sensitive to early baking rather than late baking process. The interface model contributed to dough elasticity for processes at low strain rates.